New records of three species and a variety of Angiosperms for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2020)
During the floristic explorations in Sundarbans mangrove forest of Bangladesh, conducted in 2016-2019, the authors collect some specimens of Angiosperms that are finally identified as Cleisostoma simondii (Gagnep.) Seidenf. of Orchidaceae and Volkameria heterophylla Vent. of Lamiaceae. Specimens of C. simondii are further identified as C. simondii var. guandongense Z.H. Tsi. The authors collect some specimens of another angiospermic plant in 2019 from Gazipur district of Bangladesh and confirm their identification as Leucas martinicensis (Jacq.) R. Br. of family Lamiaceae. All of these taxa are recorded here for the first time from Bangladesh. Detailed taxonomic description with notes on ecology, uses, distribution and distinctness from morphologically similar taxa, photographs and illustration are provided.Bangladesh J. Plant Taxon. 27(2): 251-260, 2020 (December)